Screening of sediment pollution in tributaries from the southwestern coast of the Río de la Plata estuary - Ronco, Alicia (2008)
Sediment chemistry and textural properties of transported materials from different surface water basins of South America has recently started to be investigated in relation to provenance materials and pollution sources. The objective of the present study is to analyze and compare pollution burdens in bottom sediments from distal positions of three drainage basins running across urban and industrialized areas and to compare them with more preserved sectors (an ups- tream position and a water stream with low anthropic influence). The surface bodies of water cross wind and water-reworked substrate materials from the Pampean loess and discharge into the Río de la Plata. Sampling was done in distal positions of the Luján and Riachuelo rivers, Canal Oeste, and Juan Blanco creek, and in Las Flores creek, a tributary of the Luján River. Standardized methods for the determination of granulometric parameters, major matrix components, and organic and inorganic pollutants were employed. Assessment of similarities between rivers by Principal Com- ponent Analysis show that distal positions of the Luján and Juan Blanco rivers and the tributary group together, and that Riachuelo and Canal Oeste split from that group by the effect of the components 1 and 2. The last two bodies of water also split from each other mainly by effect of component 2. Variables contributing most to the separation of these two bodies of water between each other are mainly given by heavy metals and sulfide. A similar behavior is also shown by cluster analysis.